2015
DOI: 10.17265/2161-6256/2015.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation and Heritability Estimates for Bunch Yield, Bunch Components and Vegetative Traits in Oil Palm Interspecific Hybrids

Abstract: Progeny testing of oil palm interspecific hybrids was conducted in four trials in Kluang, Ulu Paka, Teluk Intan and Carey Island, Malaysia. The interspecific hybrids (O  P) were created according to the North Carolina Model I (NCM I) mating design, using Elaeis oleifera (O) and Elaeis guineensis var. pisifera (P) as the maternal and paternal parents, respectively. Differences among O, P and O-within-P were determined by the performance (bunch yield, components and vegetative traits) of the progenies. There we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
1
6
1
Order By: Relevance
“…In the present study in Malaysia, MTF was in the range of 69.54 to 84.98%, with 76.77% as the trial mean. Amiruddin et al [13] reported that hybrids generally manifest low MTF and low total OTB but high STF. Progeny ECPHP618 had the highest MTF.…”
Section: Oil Palm D × P Biparental Progenies' Fruit Bunch and Its Distinctive Attributesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study in Malaysia, MTF was in the range of 69.54 to 84.98%, with 76.77% as the trial mean. Amiruddin et al [13] reported that hybrids generally manifest low MTF and low total OTB but high STF. Progeny ECPHP618 had the highest MTF.…”
Section: Oil Palm D × P Biparental Progenies' Fruit Bunch and Its Distinctive Attributesmentioning
confidence: 99%
“…Differences in genetic origins may have contributed to the decline in fruit set and a reduction in oil yield. Amiruddin et al [13] reported that the dominant gene, additive gene, or a combination of both were responsible for controlling yield due to the type of raising planting material and its growing environment. It is significant to constantly increase Malaysia's oil yield ha −1 to uphold the economic advantage in the global market [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, this research did not use an adequate experimental design for phenotype with low heritability, therefore the data found to be rather bias for those traits. The phenotype of bunch weight was found to have a low heritability value in oil palm than other phenotypes, because of great environmental factors (Din Amiruddin, Nookiah, Sukaimi, & Hamid, 2015). However, a report by Hazir & Shariff (2011) suggested that the mean bunch weight of virescens in Malaysia was 20.4 kg, with fruit weight of some 11.04 g.…”
Section: Components Of Bunch and Quantity Of Oilmentioning
confidence: 99%
“…Phenotype of mesocarp to fruit became a good indicator as selected trait because of economic value with high heritability in oil palm (Din Amiruddin, Nookiah, Sukaimi, & Hamid, 2015). The average percentage of fruit to bunch and mesocarp to fruit reached 65.39% and 37.7%, with maximum of individual reaching 70.85% and 59.6%, respectively.…”
Section: Components Of Bunch and Quantity Of Oilmentioning
confidence: 99%
“…Dwarfness, shorter fronds, disease tolerance, and resistance to climate change are among the traits contributing to increased productivity in oil palm. Some of these traits are available in the oil palm sister species, Elaeis oleifera (Amiruddin et al, 2015;Gomes et al, 2014;Hormaza et al, 2012;Montúfar et al, 2018;Sunilkumar et al, 2015). Oil palm breeders initiated interspecific hybrid breeding programmes six decades ago, aimed at reducing height increment rate, increasing oil unsaturation levels, intensifying palm oil value for diversified applications and developing disease resistance, as well as biotic and abiotic stress tolerant populations (Hardon, 1969).…”
Section: Introductionmentioning
confidence: 99%